Antibody Drug Conjugates - Bala, Stalin; Prasad, Siva K (Indian Journal of Medical and Paediatric Oncology, 2020)
Antibody drug conjugates (ADCs) are chemically engineered drugs consisting of monoclonal antibody (mAb) and cytotoxic compound attached chemically by a linker. Upon attachment to a specific target antigen, ADC enters into the cell and payload is released, which finally leads to cell killing. Payloads are broadly divided into tubulin-disrupting agents and DNA-damaging agents. Most of the current ADCs utilize humanized mAbs, and fully human mAbs are under investigation. ADC development process is accelerated by better designing and bio-engineering methods.
Keywords: Antibody drug conjugate; linker; monoclonal antibody